Characteristics of intercalary fragment in posterior malleolus fractures. Issue 3 (April 2020) - Sultan, Faisal; Zheng, Xiaodong; Pan, Zhijun; Zheng, Qiang; Li, Hang; Wang, Jianwei
Highlights: Most (45%) of intercalary fragments were between in diameter. Most (76%) of the ICF occurred in supination-external rotation subtype. The highest incidence (70%) of intercalary fragments occurs in Bartoníček type III. 31% could be accessed/removed through the gap of lateral malleolus fracture. Abstract: Background: The purpose of the study is to investigatethe prevalence of posterior malleolus intercalary fragment (ICF) in adult ankle fractures; to analyze the morphological characteristics of ICF; and its mechanism. Methods: Retrospectively, 247 cases of posterior malleolus fractures (PMF) were included in 369 cases of adult ankle fractures. The prevalence of ICF, relationship between type of ankle fracture, posterior malleolar fracture and the ICF was studied. Results: Among 369 cases, the ICF was found in 43% of the PMF and 29% of the hospitalized unstable ankle fractures. Position of ICF is posterolateral in 68 (64%), mid posterior in 20 (19%) and posteromedial in 18 (17%) cases. The prevalence of ICF was 70% in Bartoníček classification type III fractures, which was significantly higher than type I, II and IV. Conclusions: The highest incidence occurs in Bartoníček III type fracture. The study helps in further understanding and treatment of the PMF. Level of evidence: Level IV, case series.